Expanding the librarian camp-craft and skill set: Boot Camps for science and health librarians (Journal of EAHIL, 2015)
Over the past decade, “Boot Camps” have become popular among research librarians as an alternative to traditionalprofessional development venues, such as conferences. Boot Camps provide an intense immersion on current topicsof interest as well as an opportunity for onsite learning in the presence of faculty, researchers, students, and otherlibrary patrons.